THEME: DEVELOPMENT OF A METHODOLOGY CREATION OF DIGITAL TOPOGRAPHIC PLANS OF TERRAIN INCLINATION (ResearchJet Journal of Analysis and Inventions, 2021)
Every year during the rainy season, large water flows accumulate on the streets of Samarkand city. This work is devoted to the methodology development for creating digital topographic plans of the terrain slope in order to identify the rainwater accumulation on the city streets. When creating digital topographic plans of the terrain slope, stereo topographic methods were used using data from remote sensing of the Earth. The general technological scheme for creating plans based on Earth remote sensing data consists of the following stages: - editorial and preparatory work; - photogrammetric processing;- creation and updating of the terrain;- automated decryption and vectorization of data; - creation and updating of the terrain; - creation and updating of DTC and CPG baselines; - generalization of DTC and CPG to obtain derivatives (smaller) scales; - quality control and data correction; - placing DTC and CPG in a temporary archive; - updating the spatial database. Practical work was carried out at the object "Intersection of Dagbitskaya and Registan streets". Based on the performed work results, a topographic plan of the slope area was drawn up, indicating where the seasonal rainwater accumulation begins.